The Biological Use of Platelet-Rich Plasma in Skeletal Muscle Injury and Repair. Issue 5 (April 2023) - Boivin, Jordan; Tolsma, Rachael; Awad, Peter; Kenter, Keith; Li, Yong
Platelet-rich plasma (PRP) is a blood product that contains several growth factors and active proteins. PRP is thought to be used autologously to assist in the repair of injured tissues as well as to treat pain at the site of injury. The mechanism behind PRP in regenerative medicine has been well investigated and includes the identification and concentration of released growth factors and exosomes. The benefits of PRP have been highly recommended and are used widely in orthopaedics and sports medicine, including repair of injured skeletal muscle. This current report summarizes some of the more recent studies in the use of PRP as it relates to muscle healing, in both the in vitro and clinical arenas.